2006
DOI: 10.1055/s-2006-944211
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential C-N, C-C Bond-Forming Reaction: Direct Synthesis of α-Amino Acids from Terminal Alkynes

Abstract: Catalytic hydroamination is combined with the Strecker reaction to yield a one-pot synthesis of a-cyanoamines from terminal alkynes. This methodology is further applied to the synthesis of a-amino acids and a-amino esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Schafer et al also reported the synthesis of this material from its amide precursor via acid hydrolysis. 37 However, they have reported yield of <30%. Using alkaline hydrolysis pure amino acid with a reasonable yield (40%) was isolated using this synthesis method.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Schafer et al also reported the synthesis of this material from its amide precursor via acid hydrolysis. 37 However, they have reported yield of <30%. Using alkaline hydrolysis pure amino acid with a reasonable yield (40%) was isolated using this synthesis method.…”
Section: Resultsmentioning
confidence: 98%
“…The amide obtained in the previous step was further hydrolyzed to a carboxylic acid in an aqueous alkaline solution. Schafer et al also reported the synthesis of this material from its amide precursor via acid hydrolysis . However, they have reported yield of <30%.…”
Section: Resultsmentioning
confidence: 99%